Forensic medical evaluation of nasal trauma cases (Annals of Medical Research, 2022)
Aim: The purpose of this study was to evaluate the cases for which a final report was made due to nasal trauma and to reveal the errors made in the diagnosis.Materials and Methods: Among the forensic reports prepared in the Forensic Medicine Clinic of Bolu Abant İzzet Baysal University Training and Research Hospital between 2015-2019, cases with "a history of nasal trauma" were included in the study.Result: In this study, 315 cases with a history of nasal trauma were included. Two hundred sixty-four (83.8%) of the cases were male and 51 (16.2%) are female. Two hundred thirty-one of the cases (73.3%) were injured as a result of the intentional blunt injuries. Before applying to the Forensic Medicine Clinic, 28 (8.9%) of the cases were evaluated only by physical examination, 46 (14.6%) by physical examination + direct radiography, 241 (76.5%) by physical examination + direct radiography + CT. It was evaluated that the report prepared by emergency department physicians on 203 cases (64.4%) was correct, whereas the report prepared on 112 (35.6%) cases was erroneous. It was evaluated that the reports prepared by Otorhinolaryngologists on 117 cases (80.1%) were correct, whereas the reports prepared on 29 (19.9%) cases were erroneous.Conclusion: We believe that it is more appropriate to give the final forensic report of cases with nasal trauma by a Forensic Medicine Specialist rather than Emergency Department physicians or an Otorhinolaryngologist.